(untitled) (UUM Journal of Legal Studies, 2020)
Child visitation can facilitate the continued involvement of both parents in their children’s lives after a divorce. This study aims to examine the issue of visitation rights and report the results of an analysis of relevant court cases involving Malaysian Muslim families. It describes the structure or type of visitation awarded to non-custodial parents as a result of their loss of child custody. Content analysis technique was applied to elaborate on the reported court cases. A cross tabulation method was also performed to describe the frequency of cases for the respective types of visitation. This study has revealed several details about visitation rights hidden in the masses of case law. These include granted visitation rights which comprise scheduled, reasonable and dual-form visitation, counting omission of access rights which occurred most frequently including cases where parties received legal representation. The study has contributed towards a greater understanding of how visitation orders are made in practice through a quantitative analysis of past court decisions.